Factors Affecting the Demand for Chicken Eggs in Konda Konawe Selatan District During the Covid-19 Pandemic - Fyka, Samsul Alam; Bafadal, Azhar; Ahmad, Fadel (Universitas Halu Oleo, 2022)
This study aims to determine the factors that influence the demand for chicken eggs during the Covid-19 pandemic in Konda District, South Konawe Regency. Respondents in this study were 100 people who consumed purebred chicken eggs. The analytical method in this study uses multiple linear regression analysis in the form of natural logarithms. The results showed that the factors that influenced the demand for chicken eggs during the Covid-19 pandemic were the price of purebred chicken eggs, the price of fish, the average income of consumers, and the number of family members a significant effect on the demand for purebred chicken eggs. A 1% increase in the price of laying eggs will reduce the demand for laying eggs by 3.568%, a 1% increase in the price of fish will increase the demand for laying eggs by 2.604%.Keywords: demand; covid-19 pandemic; chicken eggs